Scientific practice and ordinary action ethnomethodology and social studies of science - Lynch, Michael 1948- (Cambridge University Press, 1993)
Philosophers, historians, and sociologists of science have grown interested in the daily practices of scientists. Recent studies have drawn linkages between scientific innovations and more ordinary procedures, craft skills, and sources of sponsorship. These studies dispute the idea that science is the application of a unified method or the outgrowth of a progressive history of ideas. This book critically reviews arguments and empirical studies in two areas of sociology that have played a significant role in the 'sociological turn' in science studies: ethnomethodology (the study of ordinary practical reasoning) and the sociology of scientific knowledge. In both fields, efforts to study scientific practices have led to intractable difficulties and debates, due in part to scientistic and foundationalist commitments that remain entrenched with social-scientific research policies and descriptive language. The central purpose of this book is to explore the possibility of an empirical approach to the epistemic contents of science that avoids the pitfalls of scientism and foundationalism
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Gesellschaft; Naturwissenschaft; Science / Social aspects; Science / Methodology; Sociology / Methodology; Ethnomethodology; Methode; Ethnomethodologie; Wissenschaftssoziologie; Wissenschaftstheorie